Isoglossa collina (T. Anders.) B. Hansen (Acanthaceae) - a new record for flora of Vietnam - Hai, Do Van; Huyen, Duong Duc; YUN-FEI, DENG (Academia Journal of Biology, 2012)
According to D. J. Mabberley (1997), the genus Isoglossa Oerst. has about 50 species, distributes over all the world. In the South-East Asia, the genus has 8 species, distributes from Sikkim, NE India, China, Indo-Chinese Peninsula, W. Malesia to Indonesia Ceram. Specimens belonging to the Isoglossa collina (Acanthaceae) have been found in Lam Dong province as a new record for flora of Vietnam. Thus, there are 4 separate species belong to the genus Isoglossa are acknowledged in the flora of Vietnam. Isoglossa collina has some special characters as: inflorescences terminal or axillary in axils of apical leaves, often cymose, dichotomous for many times; calyx 5-divided; corolla tube basally cylindrical, apically widen and narrowly funnel-shaped; stamens 2, included; capsule, sterile basal part, 4 ovules in cells of apical part. These specimens were collected at Lac Duong district in Lam Dong province and are preserved in the National Herbarium of the Institute of Ecology and Biological Resources, Hanoi, Vietnam (HN)